PEMBERDAYAAN MASYARAKAT DENGAN PELATIHAN KEWIRAUSAHAAN MELALUI PERAN KKN TEMATIK POSDAYA BERBASIS MASJID DUSUN SRAGI TENGAH DESA SRAGI - Endhang Suhilmiati; Anis Fauzi (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2018)
This community empowerment program is aimed at the people of Sraggi hamlet by doing entrepreneurship training, by training the wedang sari rempah to the community of PKKin the village of sragi and loundry management training specifically for the widows of the sragi village as well as screen printing and digital printing training. taught to Sragi village youth, this training was held to equip the community to be economically independent and open business opportunities for Sraggi villagers,These activities were accompanied by the college students of IAI IbrahimyGentengBanyuwangi of KKN Mosque-Based Posdaya Thematic.